Pemanfaatan media pembelajaran berbasis augmented reality menggunakan aplikasi Ar_Jarkom pada mata kuliah instalasi jaringan komputer - Elfi Tasrif; Akrimullah Mubai; Asrul Huda; Kasman Rukun (Jurnal Konseling dan Pendidikan, 2020)
This study aims to determine the level of practicality, effectiveness, and influence of the application of learning media based on Augmented Reality (AR) in the Computer Network Installation course using a mobile application called AR_JARKOM_INFORMATIKA_UNP. This study used the Research and Development (R&D) method with research subjects, namely students in class 2F3 and 2F4 of the Informatics Engineering Education Department of Electronics Engineering, Faculty of Engineering, Padang State University who attended the Computer Network Installation lectures for the January-June 2020 semester. The results of this study indicate that AR-based learning media has a practicality level of 88.40% with a very practical category, then in the effective category based on the post-test score of the experimental class (2F3) which is 73.16 which is higher than the control class (2F4) which is 69.25 and provides 33.6% contribution to the learning outcomes of Computer Network Installation based on the r square value of 0.336. So it can be concluded that AR-based learning media has a good level of practicality, effectiveness and influence to be used in the learning process of Computer Network Installation.